2007
DOI: 10.1159/000109618
|View full text |Cite
|
Sign up to set email alerts
|

Gene copy number analysis in malignant pleural mesothelioma using oligonucleotide array CGH

Abstract: Conventional cytogenetic analyses and comparative genomic hybridization have revealed a complex and even chaotic nature of chromosomal aberrations in pleural malignant mesothelioma (MM). We set out to describe the complex gene copy number changes and screen for novel genetic aberrations using a high-density oligonucleotide microarray platform for comparative genomic hybridization (aCGH) of a series of 26 well-characterized MM tumor samples. The number of copy number changes varied from zero to 40 per sample. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 62 publications
4
35
0
1
Order By: Relevance
“…In two recent array comparative genomic hybridization studies on mesothelioma patient samples, 3 of 26 and 3 of 17 tumors showed CNA at 9q. Notably, three of those cases harbored losses initiating at 9q33.1 (31,32). Furthermore, asbestos has previously been shown to cause specific breaks at the centromeric region of chromosome 9 in amniotic fluid cells (6).…”
Section: Chromosomal Microsatellitementioning
confidence: 94%
See 1 more Smart Citation
“…In two recent array comparative genomic hybridization studies on mesothelioma patient samples, 3 of 26 and 3 of 17 tumors showed CNA at 9q. Notably, three of those cases harbored losses initiating at 9q33.1 (31,32). Furthermore, asbestos has previously been shown to cause specific breaks at the centromeric region of chromosome 9 in amniotic fluid cells (6).…”
Section: Chromosomal Microsatellitementioning
confidence: 94%
“…DBC1 has been found to be downregulated by hypermethylation or loss in early stages of several other types of cancer (27 -29). CNA at 9q have been reported in 10% to 15% of mesotheliomas, a cancer type strongly associated with asbestos exposure (30,31). In two recent array comparative genomic hybridization studies on mesothelioma patient samples, 3 of 26 and 3 of 17 tumors showed CNA at 9q.…”
Section: Chromosomal Microsatellitementioning
confidence: 99%
“…MM CN analyses using whole-genome aCGH and SNP arrays revealed the presence of occasional large genomic deletions (22)(23)(24)(25)(26); however, the presence of smaller deletions [i.e., minute deletions (i.e., <3 kb)] has not been specifically investigated. Deletions in that size range fall in a gray area: they are too large to be reliably detected by NGS and Sanger sequencing and too small to be reliably detected by commercial aCGH.…”
Section: Significancementioning
confidence: 99%
“…Large-scale molecular studies of MPM have demonstrated tumor heterogeneity at the level of chromosomal abnormalities, gene mutations, epigenetic alterations, and gene expression (3)(4)(5)(6). MPM is characterized by numerous chromosomal abnormalities involving alterations in both chromosome number and structure (7).…”
Section: Introductionmentioning
confidence: 99%